Water stress alleviation effects of biostimulants on greenhouse-grown tomato fruit - Fernandes, Ângela (2022)
The aim of the present study was to evaluate the effects of three biostimulant products (Nomoren (N), Twin Antistress (TW), x-Stress (XS) and control treatment (C: no biostimulants added)) on the nutritional value, chemical composition and bioactive properties of greenhouse tomato fruit grown under full (W+: 100% of field capacity) and deficit irrigation (W–: 70% of field capacity) conditions. Fat content was the highest for the fully irrigated plants that received no biostimulants (CW+), while proteins and carbohydrates and energetic value were the highest in the XSW+ treatment. The content of the main detected sugars (fructose, glucose and trehalose) varied depending on the irrigation and biostimulant treatment. The highest amounts of individual and total organic acids and tocopherols were recorded in fully irrigated plants treated with Twin Antistress (TW), whereas the lowest overall values were observed under deficit irrigation for plants that received the XS treatment. The most abundant fatty acids were palmitic (27.5–36.0%) and linoleic acid (27.4–35.4%), followed by oleic (9.2–21.2%), linolenic (5.4–13.1%) and stearic acid (5.3–6.8%). Moreover, the highest values of -carotene and lycopene were recorded for the CW- and NW+ treatments, respectively. The TWW+ showed the highest antioxidant activity for both assays tested (TBARS and OxHLIA). Most of the tested extracts showed lower antibacterial activity against the tested bacteria compared to the positive controls. On the other hand, CW+, XSW+ and XSW- treatments showed higher antifungal activity (MIC values) than positive controls. In conclusion, each biostimulant product had a different effect on the determined characteristics depending on the level of irrigation. Therefore, more research is needed to better identify the mechanisms of action and the physiological processes, after which the tested biostimulants may be used to standardize the application of such products in tomato cultivation.